2003
DOI: 10.1167/iovs.02-1236
|View full text |Cite
|
Sign up to set email alerts
|

Functional Damage to Inner and Outer Retinal Cells in Experimental Glaucoma

Abstract: The integration of the retinal sources forming the mfERG response was compared between normal and glaucomatous monkey eyes. Both inner and outer retinal functions were aberrant in the responses of the glaucomatous eyes, with the attenuation of the inner retinal function more conspicuous. Nevertheless, glaucomatous eyes retained certain inner retinal activity, despite the advanced stage of disease. K2 responses were more sensitive to glaucomatous changes than were K1 responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 23 publications
4
33
0
1
Order By: Relevance
“…37 Similarly, delayed ERG responses and reduced amplitudes have been also shown in glaucoma. 38 Our clinical and genetic data support the hypothesis that retinal ganglion cell axon degeneration and loss of retina ganglion cells in POAG is not only due to elevated IOP alone but due to other concomitant factors compromising the survival of neuronal cell subpopulations in the inner retina as we recently reported. 14 Therefore, the putative role of RPGRIP1 as a scaffold protein regulating different signal pathways among different neuronal cell populations of the retina and its association with glaucoma makes RPGRIP1 an interesting functional candidate gene to dissect pathobiological processes underlying POAG, JOAG and NTG.…”
Section: Rpgrip1 and Primary Open Angle Glaucoma L Fernández-martínezsupporting
confidence: 90%
“…37 Similarly, delayed ERG responses and reduced amplitudes have been also shown in glaucoma. 38 Our clinical and genetic data support the hypothesis that retinal ganglion cell axon degeneration and loss of retina ganglion cells in POAG is not only due to elevated IOP alone but due to other concomitant factors compromising the survival of neuronal cell subpopulations in the inner retina as we recently reported. 14 Therefore, the putative role of RPGRIP1 as a scaffold protein regulating different signal pathways among different neuronal cell populations of the retina and its association with glaucoma makes RPGRIP1 an interesting functional candidate gene to dissect pathobiological processes underlying POAG, JOAG and NTG.…”
Section: Rpgrip1 and Primary Open Angle Glaucoma L Fernández-martínezsupporting
confidence: 90%
“…50 Ganglion cell loss and/or dysfunction on its own may not necessarily result in increased venous oxygen saturation, as other neuronal cells and supportive cells within the retinal layers require oxygen to fuel their metabolic demands. There is emerging evidence from histological, electrophysiological, and OCT studies that the processes involved in glaucomatous damage could also involve other neuronal cells such as amacrine cells, 51 bipolar cells, 50,52 horizontal cells, 53 and photoreceptors. 52,[54][55][56][57] Therefore, reduced mass tissue extraction of oxygen within the retinal layers would support our explanation of retinal venous hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results also demonstrated that the mean second-order mfERG N1 amplitudes of ring 6 was significantly reduced in eyes with macular hole compared with controls. Previous studies have found that abnormalities in the second-order mfERG response might reflect dysfunction of the inner retina, outer plexiform layer or the middle retinal layers [11][12][13][14]17]. Therefore, the observed reduction in the peripheral second-order N1 response amplitude suggested that dysfunction of the inner retina or outer plexiform layers may occur in areas beyond the macular hole.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the secondorder mfERG responses might be useful in assessing the potential dysfunction of the outer plexiform and middle retinal layers [11]. Moreover, analysis of second-order mfERG responses has demonstrated that inner retinal dysfunction might be more severe or diffuse as compared with the first-order mfERG responses in some retinal diseases [12][13][14]. The purpose of this study is to evaluate the first-and second-order mfERG responses in eyes with idiopathic macular hole and to assess the correlation between the anatomical OCT macular hole diameter and the functional mfERG parameters.…”
Section: Introductionmentioning
confidence: 99%